2021
DOI: 10.3389/fendo.2021.676403
|View full text |Cite
|
Sign up to set email alerts
|

c-Myc Upregulated by High Glucose Inhibits HaCaT Differentiation by S100A6 Transcriptional Activation

Abstract: Keratinocyte differentiation dysfunction in diabetic skin is closely related to impaired skin barrier functions. We investigated the effects of c-Myc and S100A6 on Human immortal keratinocyte line (HaCaT) or keratinocyte differentiation and potential mechanisms. The expression levels of differentiation makers such as transglutaminase 1 (TGM1), loricrin (LOR), and keratin 1 (K1) were significantly reduced, while the expression of c-Myc was significantly increased in HaCaT cells cultured in high glucose and woun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 51 publications
0
14
0
Order By: Relevance
“…HaCaT cells, which are cultured human keratinocyte cells, are commonly used to study inflammation and immunological responses in the skin [ 32 ]. In the present study, HaCaT cells were cultured under high glucose concentrations to simulate diabetic conditions [ 33 ]. M. oleifera extract did not show any cytotoxic effect on HaCaT cells in the MTT assay, confirming the results of its safety on the skin in the skin irritation test.…”
Section: Discussionmentioning
confidence: 99%
“…HaCaT cells, which are cultured human keratinocyte cells, are commonly used to study inflammation and immunological responses in the skin [ 32 ]. In the present study, HaCaT cells were cultured under high glucose concentrations to simulate diabetic conditions [ 33 ]. M. oleifera extract did not show any cytotoxic effect on HaCaT cells in the MTT assay, confirming the results of its safety on the skin in the skin irritation test.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that endothelial MYC overexpression results in severe defects in the human coronary artery (Pinheiro-de-Sousa et al ., 2022) and the embryonic vascular system (Kokai et al ., 2009). Similarly, high glucose has been shown to activate MYC target genes in different cell types (Jonas et al ., 2001; Zhang et al ., 2021), resulting in exaggerated cell proliferation. Of note, Myc is not only an oxidative stress-responsive gene (Elouil et al ., 2005), but it can also induce ROS production (Vafa et al ., 2002; Liu et al ., 2017).…”
Section: Discussionmentioning
confidence: 99%
“…34 In vitro study showed that high glucose inhibited the expression levels of transglutaminase 1 and loricrin in keratinocyte cultures. 35 Thus, decreased expression levels of differentiation-related marker proteins can contribute to delayed permeability barrier recovery. The delayed permeability barrier recovery in mice and humans with type 2 diabetes can be attributed to elevated skin surface pH (discussed later), 15,16,36 and reduced hyaluronic acid, 37 which is required for epidermal lipid production, keratinocyte differentiation, and proliferation.…”
Section: Epidermal Permeability Barriermentioning
confidence: 99%
“…In addition, expression levels of loricrin and filaggrin are decreased in diabetic mice 34 . In vitro study showed that high glucose inhibited the expression levels of transglutaminase 1 and loricrin in keratinocyte cultures 35 . Thus, decreased expression levels of differentiation‐related marker proteins can contribute to delayed permeability barrier recovery.…”
Section: Alterations In Epidermal Functionsmentioning
confidence: 99%